From Reactive Religious Identities to Camouflage: Exploring Daily Encounters with Racism and their Impact on Identification Strategies for Spanish-born Descendants of Moroccans - Rodríguez-Reche, Cristina (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2025)
The rejection of the North African community in Spain, chiefly from Morocco, constitutes one of the most deeply rooted expressions of racism in the country. This racialisation process relies on visible and stereotypical markers perpetuating a colonial, homogeneous and essentialist category around the image of the “Moor”. However, the relationship of experiences of individuals within this community in dealing with everyday racism, their protective resources, and the resulting impact on their identification strategies remain underexplored. Based on 31 in-depth interviews with descendants of Moroccan immigrants and children of mixed couples, this paper aims to explore the role daily Islamophobia plays in identification processes and survival strategies. The findings highlight the main patterns from this analysis: reactive religious identity, misrecognition with horizontal hostility as the leading cause, camouflage and passing and, finally, self-chosen identification. This contribution underscores the often-overlooked role of everyday racism in people’s lives and emphasises its impact on the sense of belonging among the young people interviewed.